2003
DOI: 10.1189/jlb.0403141
|View full text |Cite
|
Sign up to set email alerts
|

ADAM-17-independent shedding of L-selectin

Abstract: L-selectin is expressed by leukocytes and facilitates their adhesion under flow along the walls of blood vessels. As do a variety of membrane proteins, L-selectin undergoes ectodomain shedding. Using approaches that monitor full-length L-selectin in short-term assays, it has been determined that L-selectin shedding is defective in tumor necrosis factor alpha-converting enzyme (ADAM-17)-deficient cells. In this study, we examined the steady-state levels of L-selectin on ADAM-17-deficient cells using a monoclona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 55 publications
(103 reference statements)
2
44
0
Order By: Relevance
“…This methodology was shown previously to be insensitive to topographic redistribution of L-selectin (72). We also engineered a deletion in the cleavage region of ⌬16 Lselectin, which we reported previously blocks L-selectin shedding (52,82). Despite this cleavage resistance, we found that the adhesion defect by ⌬16 L-selectin was not altered (Fig.…”
Section: Conserved Cationic Motif In Cytoplasmic Region Of L-selectinmentioning
confidence: 64%
See 1 more Smart Citation
“…This methodology was shown previously to be insensitive to topographic redistribution of L-selectin (72). We also engineered a deletion in the cleavage region of ⌬16 Lselectin, which we reported previously blocks L-selectin shedding (52,82). Despite this cleavage resistance, we found that the adhesion defect by ⌬16 L-selectin was not altered (Fig.…”
Section: Conserved Cationic Motif In Cytoplasmic Region Of L-selectinmentioning
confidence: 64%
“…Flow cytometry, immunoprecipitation, SDS-PAGE, and immunoblotting were performed as previously described (1,52,74,82,84). For flow cytometry, antibody-labeled cells were analyzed (10,000 cells/sample) or sorted on a FACSCalibur instrument (Becton-Dickinson Immunocytometry Systems, San Jose, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Within tissues, neutrophil degranulation is a rich source of serine proteases, and their release may significantly contribute to the loss of L-selectin once they are within the peritoneum. Because some Adam17-independent cleavage of L-selectin can be inhibited by metalloproteinase inhibitors, 35 it is possible that there may be a shift in the enzymes controlling L-selectin cleavage as the inflammatory response evolves and/or at different steps in the emigration process. Recently, Adam8 mobilization from the neutrophil granules to the membrane was demonstrated after endothelial adhesion, and Adam8 increased L-selectin shedding.…”
Section: Discussionmentioning
confidence: 99%
“…For such an assay system, antibodies against the ϳ13-kDa C-terminal portion of the GPV ectodomain will be required that are currently being generated in our laboratory. ADAM 17 is a well known sheddase that cleaves a variety of receptors, including L-selectin, VCAM-1 (14,33,34), and, as shown very recently, platelet GPIb␣ (35). As in the regulation of these molecules, the release of GPV from the platelet surface can be stimulated by the phorbol ester PMA through activation of ADAM17, a pathway that seems to be conserved across multiple cell types.…”
Section: Fig 4 Gpv Shedding Is Abolished In Adam17mentioning
confidence: 99%